A Study on Tea Plantation Worker’s Health, Safety and Welfare Measures of Tea Estates with Reference to Nilgiris District, Tamilnadu - S. Senthil Kumar, Dr. C. Vellaichamy (International Journal of Advanced Science and Technology, 2020)
Tea is the most preferable common by millions of people across the globe. In India, Tea plantation is situated in Darjeeling and Assam, Terai and Dooars in the North Bengal and Mysore, Coorg, Manjsholai and Nilgiris. The Tea industry in India has given profession to the foremost work force in which Nilgiri is also acquiring a part. Tea is a natural product and virtually calorie-free when smashed without milk and sugar. Over the last few decades, tea has become one of India’s most significant commodities. The Indian tea industry is nearly 200 years old. The recognition for creating India’s vast tea empire goes to the British, who discovered tea in India. Tea is grown in the states viz. Assam, West Bengal, Tamilnadu, Kerala, Karnataka, Tripura, Himachal Pradesh, Uttar Pradesh and Bihar. However, making in substantial quantities is restricted to the first five states. Tea plantation in Tamilnadu is mostly concentrated in Nilgiris district due to encouraging agro-climatic conditions. In tea industry, the tea plantation workers approach in the category of ’wage plantation workers’. Workers health, safety and welfare are the measures of inspiring the effectiveness of workers. The health, safety and welfare measures endow with the tea plantation estates and the concern will have instant effect on the health, physical and mental efficiency attentiveness, confidence and inclusive efficiency of the worker. Working class requires proper health and safety measures for better work efficiency. Tea plantation and production plays a noteworthy task in Indian economy. Plantation workers are definitely as important to plantation industry as producers, dealers and consumers. In India, Welfare measures play a essential role in enhancing the health and efficiency of the plantation workers. The research of the study highlights the health, safety and welfare measures provided and also to recognize the level of benefits given to the tea plantation workers by the tea plantation estates. The cultivation of tea is essentially based on the tea plantation workers and the study is to analyze about the problems of tea plantation workers in Nilgiris District. The consequence of considering these factors is analyzed and recommended as per the results conditional from several tea estates resides in Nilgiris District. Convenient sampling technique is practical and expressive type of research is undertaken to determine the worker’s health, safety and welfare measures of the tea plantation workers of tea estates in Nilgiris District.